ANALISA KERUSAKAN TRACK ADJUSTER EXCAVATOR EX 2600-6 PADA DIVISI REMANUFAKTUR PT. HEXINDO ADIPERKASA Tbk. - , MAULIDHA PRASETIYO, Radhian Krisnaputra, S.T., M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Track adjuster placed in undercarriage, so it working heavy and occurs frequently. Because of it, we have to know the working principle and performed analysis of the damage on track adjuster excavator EX 2600-6, so the damage can be minimized and the unit can work well. Having performed of the disassembly of track adjuster EX 2600-6 which is track adjuster is one of the main hydraulic components. The failure was initiated to inner parts track adjuster discoloration, in the form of pitting, erosion, and scratch. 30% failure of machine caused by maintenance error, and 70% hydraulic system failure caused by misstep of using hydraulic oil and contamination factor. The failure on track adjuster excavator EX 2600-6 caused by working disruption such as, external leak, internal leak, and contamination conducing the deficiency of hydraulic system. So it is preventing can be performed by using recommended hydraulic oil, maintenance performance and treatment of the undercarriage, the proper operational unit, and improvement.